Evolution of thermal stress-related traits in hybrids of Drosophila jambulina and D. punjabiensis. Issue 1 (2nd January 2020) - Ramniwas, Seema; Kumar, Girish; Singh, Divya
Abstract : Using two sibling species, Drosophila jambulina and D. punjabiensis, interspecific crossabilty were examined in natural as well as laboratory conditions. Collection record showed that hybrids are found only in specific hybrid zone having higher temperature variation suggesting an increased fitness in hybrid zone. In laboratory condition, plastic effects on thermo-tolerance traits (heat knockdown and cold recovery) were investigated by growing parental species [ D. jambulina and D. punjabiensis at four growth temperatures (17 to 28 °C)] and their hybrids at six growth temperatures (15 to 31 °C). Hybrids showed higher plasticity for melanization ( 58%) and thermo-tolerance traits (CV = 39.14 for heat resistance and CV = 43.15 for cold resistance) at different growth temperatures. Acclimation effects were also significant in hybrids ( F = 47.89 for heat resistance and F = 56.87 for cold resistance) suggesting an adaptive potential. Results of this study imply that hybridization increases genetic variation which in turn leads to adaptation to new environments. The genetic data obtained in this study would be useful not only for testing basic predictions about evolution but also for understanding the evolutionary significance of hybrids.